Implementasi strategi pemasaran dalam meningkatkan aksesibilitas perbankan syariah - kamilah, nila farchatul (Maliki Interdisciplinary Journal, 2025)
Islamic banks are financial institutions whose operations are based on the principles of Islamic law, providing credit services and financial transactions in accordance with sharia rules. Islamic banks in Indonesia have grown rapidly since the issuance of Law No. 21/2008 on Islamic Banking, which provides a strong legal foundation for Islamic banks. This development is also supported by other laws such as State Sharia Securities (SBSN), Law on Religious Courts, Waqf, and Zakat. The marketing strategy of Islamic banks is very important in increasing the accessibility of Islamic banking services. The implementation of marketing strategy involves planning the vision and mission, identifying internal strengths and weaknesses, setting long-term goals, and selecting effective strategies. In practice, Islamic banks should set annual goals, formulate policies, promote human rights, and ensure resource allocation for strategy implementation. The importance of regulation and coordination between countries in developing the Islamic finance industry cannot be underestimated. The Indonesian Ulema Council (MUI) also plays a significant role with its fatwas that serve as a reference for Islamic finance regulations. The integration of modern technology and productive promotion can increase efficiency and customer participation in using Islamic banking services.